GAYA KEPEMIMPINAN CAMAT DALAM MEMPENGARUHI KINERJA PEGAWAI - Deviandi E.42008043, Erik (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
AbstractThis  research  is  intend  to  know  about  the  leadership  style  of the  leader  in  improvement  of  employee’s performance in Ledo Sub-District Office Bengkayang Regency. In this case can be seen that the role and task of the head of Ledo Sub-District is try to affect the employees to keep working effectively in accordance with the time and goals target. In other words, level of employee’s work effectiveness is depend on the way or attitude of the head of sub-district in    the lead action or the activities that needed to be done in order to make the employees are willing to follow all of his will to reach the goals of organization.Based on that background, so the formulation of the problem is how the effective leadership style can improvethe employee’s performance in Ledo Sub-District Office Bengkayang Regency. Thus, the goal of this research is to identify and to describe the leadership style of the head of sub-district in improvement of employee’s performance in Ledo  Sub-District  Office  Bengkayang  Regency.  The  research  method  that  used  in  this  research  is  qualitative descriptive  methods  and  data  collection  techniques  by  interview,  observation  and  study  documentation.  The informant in this research is one main informant and 9 other informants.The conclusion of this research shows that the head of Ledo Sub-district’s leadership style for the present time is not effective yet in implementation, in the meaning of the relationship between the superior and subordinate, from the side of communication, motivation, division of work and giving responsibility, work assessment and leader’s controlling action    still  can’t implemented  perfectly.  The  employee’s performance  in Ledo  Sub-District  Office Bengkayang Regency is still not too good and still  can’t make  satisfaction.  This can be seen clearly from the completion of the work which is not on time, unsatisfactory work result and lack of the provision of public services. Plus limited and minimum facilites making it difficult for the employees to finish their work.Keywords : Leadership Style and Performance